Analisa Kualitas Layanan Perpustakaan UIN Sunan Kalijaga Yogyakarta dengan Metode LibQual dan WebQual - Khotimah, Khusnul; Astuti, Sri; Ismiyatin (Pustakaloka, 2024)
Libraries for universities are an inseparable part because they are a reflection of the university in providing services. Commitment to service quality is needed so that managers always try to meet the expectations of their users. The service quality can be improved, one of the ways is by collecting important information from users about the services provided. The methods used to collect the information in the research were LibQual and WebQual. The purpose of the research was to determine user perceptions of the service quality and web services in UIN Sunan Kalijaga Yogyakarta Library. The samples of the research were 100 users in UIN Sunan Kalijaga Yogyakarta Library which was determined using accidental sampling technique. The number of samples was obtained using the Taro Yamane formula with a 10% error margin. The data was obtained by distributing questionnaires and were measured using a Likert scale. Results of the research show that the service quality of the UIN Sunan Kalijaga Yogyakarta Library from the dimensions of service effect, control of information, and library as the place is very good with an average value of 3.47. The web quality of UIN Sunan Kalijaga Yogyakarta Library, which consists of quality of usability, quality of information, and quality of interaction, is very good, with an average score of 3.39. Things that library managers need to pay attention to are UIN Sunan Kalijaga Yogyakarta Library as the place for entertainment/recreation and a web display that is considered less attractive. The value of each item is 3.07 and 3.21, which means it is below the average value of this study.